Ceftriaxone-induced severe hemolytic anemia, renal calculi, and cholecystolithiasis in a 3-year-old child: a case report and literature review - Tao, Enfu; Zhou, Huangjia; Zheng, Meili; Zhao, Yisha; Zhou, Junfen; Yuan, Junhui; Yuan, Tianming; Zheng, Changhua (Frontiers in Pharmacology, 2024)
Ceftriaxone is widely used in pediatric outpatient care for its efficacy against respiratory and digestive system infections, yet its increasing association with severe immune hemolytic reactions requires heightened vigilance from pediatricians. This report details a rare and severe case of ceftriaxone-induced severe immune hemolytic anemia (IHA), hemolytic crisis, myocardial injury, liver injury, renal calculi, and cholecystolithiasis in a previously healthy 3-year-old child. The child, treated for bronchitis, experienced sudden pallor, limb stiffness, and altered consciousness following the fifth day of ceftriaxone infusion, with hemoglobin levels precipitously dropping to 21 g/L. Immediate cessation of ceftriaxone and the administration of oxygen therapy, blood transfusion, intravenous immunoglobulin (IVIG), and corticosteroids led to a gradual recovery. Despite initial improvements, the patient's condition necessitated extensive hospital care due to complications including myocardial injury, liver injury, and renal calculi, and cholecystolithiasis. After a 12-day hospital stay and a three-month follow-up, the child showed complete normalization of hemoglobin and liver function and resolution of calculi. In children, ceftriaxone infusion may trigger severe, potentially fatal, hemolytic reactions. Pediatricians must promptly recognize symptoms such as pallor, limb stiffness, and unresponsiveness, indicative of ceftriaxone-induced severe IHA, and immediately discontinue the drug.Effective management includes timely blood transfusion, respiratory support, IVIG administration, and corticosteroids when necessary, along with rigorous vital signs monitoring. Continued vigilance is imperative, even after cessation of ceftriaxone, to promptly address any residual adverse effects.